1997
DOI: 10.1038/385272a0
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of inactivation gates from mammalian voltage-dependent potassium channels

Abstract: The electrical signalling properties of neurons originate largely from the gating properties of their ion channels. N-type inactivation of voltage-gated potassium (Kv) channels is the best-understood gating transition in ion channels, and occurs by a 'ball-and-chain' type mechanism. In this mechanism an N-terminal domain (inactivation gate), which is tethered to the cytoplasmic side of the channel protein by a protease-cleavable chain, binds to its receptor at the inner vestibule of the channel, thereby physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 21 publications
5
70
0
1
Order By: Relevance
“…Although C 13 xxH 16 is located in the very flexible transition between the N-terminal domain and the helix, H35 is in the center of the helix. This observation is consistent with the study by Antz et al (36), where it was shown that a peptide encompassing the inactivation domain of Kv1.4 possesses a highly flexible disordered N terminus and a well-defined helix. Based on CD measurements and NMR data in aqueous solution, Pep61 is even more flexible and disordered at body temperature (37°C) compared with 10°C, and this flexibility enables the distal end to enter the cavity from the intracellular side.…”
Section: Discussionsupporting
confidence: 82%
“…Although C 13 xxH 16 is located in the very flexible transition between the N-terminal domain and the helix, H35 is in the center of the helix. This observation is consistent with the study by Antz et al (36), where it was shown that a peptide encompassing the inactivation domain of Kv1.4 possesses a highly flexible disordered N terminus and a well-defined helix. Based on CD measurements and NMR data in aqueous solution, Pep61 is even more flexible and disordered at body temperature (37°C) compared with 10°C, and this flexibility enables the distal end to enter the cavity from the intracellular side.…”
Section: Discussionsupporting
confidence: 82%
“…4A). This structure is similar to the 37 amino acid piece we reported earlier (18) with the exception that the ␣-helix is extended by 2 turns and bent in its center. The C-terminal domain of Kv1.4N-(1-75) equivalent to the stretch harboring ID2 (20) consists of a 2.5-turn ␣-helix between amino acids 41 and 49 connected to a flexible domain formed by residues 50 -75 (Fig.…”
Section: Methodssupporting
confidence: 63%
“…The PEVK region is very likely to be structurally disordered and may function as a rubber-like entropic spring that helps to restore over-stretched muscle cells to their natural, relaxed length. 225 K 226,227,228 The timing of this closure is critical to proper nerve cell function and evidently depends on the length and flexibility of the chain. Here we suggest that this flexiblity be recognized as an entropic clock due to its important function as a timing device.…”
Section: Interesting Functions Associated With Disordermentioning
confidence: 99%